Reclassification of variants of uncertain significance by race, ethnicity, and ancestry for patients at risk for breast cancer - Pleasant, Versha; Boggan, Jordyn; Richards, Blair; Milliron, Kara J.; Purrington, Kristen S.; Simon, Michael; Merajver, Sofia (Frontiers in Oncology, 2025)
IntroductionAlthough most variants of uncertain significance (VUS) in breast cancer susceptibility genes are eventually downgraded to benign or likely benign in individuals of European ancestry, it is unclear if this also applies to non-European populations. This study examines the time to and type of VUS reclassification among a diverse cohort at risk for breast cancer.MethodsA multicenter retrospective analysis examined people assigned female at birth (AFAB) who underwent genetic testing from 2013 to 2021 with VUS in ATM, BARD1, BRCA1/2, CDH1, CHEK2, NF1, PALB2, PTEN, RAD51C/D, STK11, and/or TP53. Demographic data were collected [including race, ethnicity, and ancestry (REA)], as well as time to and type of reclassification. Frequency data and univariable and multivariable analyses were performed (p < 0.05 was considered statistically significant).ResultsThere were 932 participants who had a total of 1,032 VUS (905 unique variants), with 20% who underwent reclassification of their results. The proportion of reclassified VUS among the largest represented REA groups was 19%, 23%, and 27% for White, Black or African American, and Asian people, respectively. REA was not associated with VUS reclassification (p = 0.25). The mean time to VUS reclassification was 2.8 years and was not significantly associated with REA (p = 0.16). Most VUS were downgraded to benign/likely benign (n = 187, 92%).DiscussionOur findings demonstrate that REA is not significantly associated with VUS reclassification or time to reclassification, with the majority of VUS being downgraded across REA. This study allows for improved and more equitable genetic counseling. It may also provide more reassurance to those groups that may have a higher likelihood of VUS results.